Learning Styles of First Year Nursing and Midwifery Students in Ilam University of Medical Sciences - Hadi Peyman; Jamil Sadeghifar; Maryam Alizadeh; Monireh Yaghoubi; Monireh Mohammad Hassan Nahal; Nikoo Yamani; Ali Delpisheh (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Learners have very different learning styles depend on their preference, psychological preparedness as well as physical condition of their senses. Identification of proper learning styles plays an important role for choosing effective teaching methods, transferring concepts, and finally improving education quality. This study aimed to identify learning style of first year nursing and midwifery students in Ilam University of medical science. Methods: In this cross-sectional study, 50 first year nursing and midwifery students at Ilam University of Medical Sciences were studied, in 2009. Data collection was done using VARK questionnaire. Results: 56% of samples (n=28) were female. 44% (22 students) preferred a single learning style (Uni-modal) and 56% preferred multi-modal learning styles. Students, who preferred only one style, preferred reading/writing style to other styles. While other students who preferred more than one styles, used quad-modal. Conclusion: In this study, the preferred learning styles were reading/writing, aural, kinesthetic and visual, respectively. Determination of desired learning styles of first- semester students can be helpful for choosing appropriate teaching methods by educational groups and faculty members, which lead to achieving educational goals.